2009
DOI: 10.1897/09-042.1
|View full text |Cite
|
Sign up to set email alerts
|

A model predicting waterborne cadmium bioaccumulation in Gammarus pulex: The effects of dissolved organic ligands, calcium, and temperature

Abstract: Metal bioavailability depends on the presence of organic ligands in the water and on the concentrations of competitive cations. The present study aims at testing whether the diffusive gradient in thin films technique (DGT) could be used to take into account Cd speciation and its consequences on bioavailability in a bioaccumulation model and whether the influences of the Ca concentration and temperature also should be considered. Four kinetic experiments were conducted on Gammarus pulex: a calibration of Cd tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…This result corroborates previously published observations that Cd is accumulated through high affinity Ca channels [5] and inhibits the uptake pathway of this cation [32]. The competitive effect between Ca and Cd for binding sites on the gills' surface has been reported in various other species [5,7], as well as the competitive effect between Cd and Zn [8,31].…”
Section: Effect Of Ca and Zn And Modeling Establishmentsupporting
confidence: 92%
See 1 more Smart Citation
“…This result corroborates previously published observations that Cd is accumulated through high affinity Ca channels [5] and inhibits the uptake pathway of this cation [32]. The competitive effect between Ca and Cd for binding sites on the gills' surface has been reported in various other species [5,7], as well as the competitive effect between Cd and Zn [8,31].…”
Section: Effect Of Ca and Zn And Modeling Establishmentsupporting
confidence: 92%
“…Indeed, the bioaccumulation and toxicity of Cd are modulated by different parameters such as Ca, Zn, and dissolved organic carbon (DOC) concentrations. Different studies reported a decreased bioaccumulation of Cd in different species when Ca concentration increased: Daphnia magna [4], Corbicula fluminea [5], Lymnea stagnalis [6], and Gammarus pulex [7]. It was also demonstrated that Zn had a protective effect on Cd toxicity [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…These predictive models are generally constructed in the laboratory by the establishment of kinetic parameters describing physiological mechanisms involved in the uptake of bioavailable metals and elimination of bioaccumulated metals. Such mechanistic approaches were successfully performed in various aquatic species including gammarids (Croteau and Luoma 2007;Liu et al 2002;Pellet et al 2009;Worms et al 2006). The major forms of bioaccumulated metal are represented by the free ions, which can directly interact with transport sites and across the biological membranes of aquatic organisms (Niyogi and Wood 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5), which are thus mobile and available for aquatic organisms, as showed for gammarids with Cd and Cu (Pellet et al, 2009;Ferreira et al, 2013). For Cr and Pb, the increase in bioaccumulation could be explained by the enrichment of the effluent of pumping/dilution in organic matter and changes in SPM properties, hence enhancing their particulate bioavailability and subsequently their assimilation by mussels (Roditi et al, 2000;Bourgeault et al, 2010a;Bourgeault et al, 2011).…”
Section: Impact Of Dredging On Metal Bioaccumulationmentioning
confidence: 92%
“…Among the chemical tools that have been developed, the Diffusive Gradient in Thin-films technique (DGT) is a speciation method that allows for the estimation of time-weighted average concentration of labile metals through in situ passive sampling (Tusseau-Vuillemin et al, 2007; Uher et al, 2011). The DGT-labile metallic fraction, which is composed of free inorganic metals and weak organic complexes, has been shown to be close to the bioavailable fraction for freshwater organisms exposed only by aqueous route (Ferreira et al, 2009;Pellet et al, 2009). In terms of biological tools, bioaccumulation studies using encaged organisms have gained importance for environmental risk assessment (Bervoets et al, 2005;Besse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%